Chemical Evidence of Prehistoric Passive Tobacco Consumption by a Human Perinate (Early Formative Period, South-Central Andes) - Echeverria-Morgado, J (Elsevier Inc., 2018)
Consumption of psychoactive substances is a long-standing tradition among indigenous peoples of the Americas. Archaeologically, consumption of tobacco has been shown through analysis of archaeological smoking pipe residues, mummy hair and dental calculus. Analysis of the hair of a perinate recovered from a rock shelter in Northern Chile and dated ca. 2400 yrs BP showed the presence of nicotine and its main metabolic product, cotinine. Quantitative segmental hair analysis showed that nicotine was taken up from the mother via the placenta and not through breast milk and that the death of the perinate occurred soon before or at the time of delivery. The analysis also indicated that the mother consumed high quantities of tobacco, suggesting she was a “tobacco shamaness” who might have experienced a miscarriage, since tobacco consumption by pregnant women is strongly associated to spontaneous abortions and perinatal death. Thus, at the dawn of pastoralism and agriculture in the highlands of the Atacama Desert, female individuals were already intensively consuming this psychoactive plant, transmitting its signals, and perhaps its lethal effects, to a child during gestation. This is the first evidence of simultaneous presence of nicotine and cotinine in pre-Hispanic bioanthropological remains from the Americas, thus constituting unequivocal direct evidence of tobacco consumption, and it refers to the currently earliest and youngest passive tobacco consumer in the Americas. © 2018